Optimizing Drug Adherence and QoL of Pulmonary Tuberculosis Patients through Structured Health Education Based on Peer Group Support - Mantouw, Frely; Indasah; Widyowati, Agustin (Journal of Applied Nursing and Health, 2024)
Background: Patients with pulmonary tuberculosis frequently experience issues like non-compliance with treatment, boredom from prolonged therapy, and stopping treatment due to lack of recovery. This non-compliance can lead to drug resistance, therapy failure, reduced quality of life, and a higher risk of death. This study aimed to investigate the effects of Structured Health Education combined with Peer Group Support on medication adherence and quality of life among pulmonary tuberculosis patients. Methods: This quantitative study employed an actual experimental research design with a pretest-posttest control group approach. The research included 38 respondents as the sample. The independent variable was Structured Health Education with Peer Group Support, while the dependent variables were Medication Compliance and Quality of Life. The research instruments used included the Morisky Medication Adherence Scale-8 (MMAS-8) to measure medication compliance and the WHOQOL-BREF to assess quality of life. The Mann-Whitney Test was applied to test the study's hypotheses. Results: Structured Health Education based on peer group support is efficacious in improving patients' medication adherence and quality of life with pulmonary tuberculosis. Conclusion: Nurses in the outpatient room of the health centre can apply the results of this study in providing nursing interventions and structured health education based on peer group support to improve medication adherence and the quality of life of patients with pulmonary tuberculosis.